2023
DOI: 10.1093/cvr/cvad147
|View full text |Cite
|
Sign up to set email alerts
|

Predictive metabolites for incident myocardial infarction: a two-step meta-analysis of individual patient data from six cohorts comprising 7897 individuals from the COnsortium of METabolomics Studies

Ana Nogal,
Taryn Alkis,
Yura Lee
et al.

Abstract: Aims Myocardial infarction (MI) is a major cause of death and disability worldwide. Most metabolomics studies investigating metabolites predicting MI are limited by the participant number and/or the demographic diversity. We sought to identify biomarkers of incident MI in the Consortium of Metabolomics Studies (COMETS). Methods and Results We included 7,897 individuals aged on average 66 years from six intercontinental cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Metabolomics studies have identified several dysregulated metabolites during MI, including lipids, amino acids, energy metabolites, and oxidative stress markers (189)(190)(191). Research has revealed notable distinctions in metabolite profiles between patients with MI and healthy individuals or other populations (192,193). Some metabolites, such as 12,13-diHOME, noradrenaline, tryptophan, and cysteic acid, were significantly elevated in patients with MI, while some antioxidants like glutathione were decreased (194)(195)(196).…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomics studies have identified several dysregulated metabolites during MI, including lipids, amino acids, energy metabolites, and oxidative stress markers (189)(190)(191). Research has revealed notable distinctions in metabolite profiles between patients with MI and healthy individuals or other populations (192,193). Some metabolites, such as 12,13-diHOME, noradrenaline, tryptophan, and cysteic acid, were significantly elevated in patients with MI, while some antioxidants like glutathione were decreased (194)(195)(196).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Research has revealed notable distinctions in metabolite profiles between patients with MI and healthy individuals or other populations ( 192 , 193 ). Some metabolites, such as 12,13-diHOME, noradrenaline, tryptophan, and cysteic acid, were significantly elevated in patients with MI, while some antioxidants like glutathione were decreased ( 194 196 ).…”
Section: Single-omics Approachesmentioning
confidence: 99%
“…This is in line with other prospective and MR studies demonstrating potentially harmful effects of higher plasma BCAA levels, as well as lower plasma glycine levels on the development of hypertension, myocardial infarction, and coronary heart disease (CHD). [17][18][19][20][21] Proinflammatory and pro-oxidant effects of tBCAAs, as opposed to the potentially counteracting effects of glycine, might provide an explanation for these associations. [22][23][24] Given the fact that plasma metabolites, including amino acids, form a complex network of mutual relationships and participate in numerous biochemical cycles, 25 analyzing their ratios may provide novel information on the genetic determinants of particular metabolites and their shared biology, together with links to the disease.…”
mentioning
confidence: 99%
“…This is in line with other prospective and MR studies demonstrating potentially harmful effects of higher plasma BCAA levels, as well as lower plasma glycine levels on the development of hypertension, myocardial infarction, and coronary heart disease (CHD). 17 21 Proinflammatory and pro-oxidant effects of tBCAAs, as opposed to the potentially counteracting effects of glycine, might provide an explanation for these associations. 22 24 …”
mentioning
confidence: 99%